The Scorch Trials - Dashner, James, 1972- (New York : Delacorte Press, 2010)
After surviving horrific conditions in the Maze, Thomas is entrapped, along with nineteen other boys, in a scientific experiment designed to observe their responses and gather data believed to be essential for the survival of the human race.
Sequel to: The maze runner.
Keywords: Survival skills -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; Science fiction